Unpacking the Impact of the COVID-19 Pandemic in Zimbabwe`s Public Sector - Dr., Alouis Chilunjika; Muzvidziwa-Chilunjika, Sharon; Mutizwa, Bismark (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The novel COVID-19 pandemic has ravaged the entire world and its far reaching impacts have been felt across different regions and sectors world-over. Similarly, the Zimbabwean public sector has been equally affected by this pandemic. Using a qualitative methodology the research interrogates the effects of the COVID-19 pandemic and proffers ways to deal with its impacts on the Zimbabwean public sector. Data was extensively collected from documentary sources such as books, journals, government publications etc. The study established that the Zimbabwean Health Sector (ZHS) is completely overwhelmed by the pandemic, that there is a decrease in revenue collection, poor social accountability, and corruption and that frontline employees and those working in environments that are exposed to the virus are psychologically affected. The research recommends that the government should capacitate the ZHS, revitalise industries and harnessing small to medium enterprises, embrace open Information Technologies (I.T) in parliamentary activities, strengthen the Watchdog institutions and create sustainable conducive working conditions for all.